Diatoms from DH-7B sediment core from the Dahu Lake, Ilan Plain - Rahman, Abdur; Wang, Liang-Chi; Kashima, Kaoru; Li, Hong-Chun; Chen, Huei-Fen; Yang, Tien-Nan (In: Rahman, A et al. (2025): Typhoon and climate history of northeastern Taiwan during mid to late Holocene: inferred through the Dahu Lake sediment core, Ilan Plain [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982469, 2025)
A 35-meter-long sediment core (DH-7B) was retrieved from Dahu Lake using a stainless-steel pipe mounted on a floating platform. The core was subsampled at 5-cm intervals with 1-cm thickness for diatom, stable isotope, and trace element analyses. For diatom analysis, 0.5 g of dry sediment was treated with 32% H₂O₂ and 10% HCl. The cleaned material was mounted on slides using Wako mounting medium, and 300 diatom valves were identified and counted under an optical microscope at 1000× magnification.
Keywords: Diatom; Geochemistry; Stable isotope